Hysteretic Performance of Composite Damper with Yielding Reserve Stiffness - Xiaorui Zhang; Lihua Zhu; Libo Liu; Jialong Li (Buildings)
Previous research on composite dampers has rarely addressed the issue of large deformations of structures under limit state. However, the proposed damper in this paper takes this issue into account and could provide yielding reserve stiffness for structures, ensuring structural resilience. A composite damper with yielding reserve stiffness (YRSD), consisting of a friction unit and a metal yield unit, was proposed. Low cyclic loading tests with different energy-dissipating steel plate thicknesses and bolt preloads were carried out and experimental results were compared with that of numerical simulation. This paper focuses on the synergistic energy dissipation mechanism of the proposed damper and the effects of various factors on its hysteretic performance, including the bolt preload and thickness of X-shaped steel plates. The results show that the synergistic energy dissipation mechanism of the proposed damper is well, exhibiting the behavior of hardening post-yielding stiffness and multi-stage energy dissipation characteristics, which could provide yielding reserve stiffness for the structure. The experimental hysteresis curve of YRSD is full, indicating its strong energy dissipation capacity, and the skeleton curve of experiment is consistent with that of the theoretical model. The envelope area of the rectangular hysteresis curve of YRSD increases by 107.3% with the preload increased by 100%. When the thickness of the X-shaped steel plates is increased by 2 mm, the resistance of YRSD increases by 26.2% and the post-yield stiffness increases by 37.9%. The stiffness degradation trend of all specimens initially decreases and then increases. The energy dissipation capacity of the friction unit increases by 53.8% as the preload is doubled. The capacity of the metal yield unit increases by 31.7% as the thickness of the X-shaped steel plates is increased by 2 mm. When the energy dissipation capacities of the friction unit and the metal yield unit are close to equal, the optimal energy dissipation capacity of the proposed damper is achieved. The error of results between the numerical analysis and experimentation is less than 10%, providing a basis for the parametric analysis of similar composite damper with yielding reserve stiffness.